Pelatihan Pembuatan Sabun Cuci Tangan Cair bagi Jemaat GPIA Keluarga Allah Sidoasri - Budi Tjahjadi; Rena Rena; Dyah Erwina Hadiningtyas (Institut Nalanda, 2026)
The training on liquid hand soap making was conducted at Gereja Pantekosta Isa Almasih (GPIA) Keluarga Allah, Sidoasri, Malang, East Java. This community service was motivated by the increasing need for hand soap as a hygiene product, especially during and after the COVID- 19 pandemic. The program was carried out in three stages: an interview and observation phase in November, followed by a two-day training session on January 21–22, 2026, and a follow-up evaluation in March and April 2026. A total of ten participants took part, consisting of six women and four youth. During the training, participants learned about raw materials, composition, production methods, packaging, and product marketing. The cost of raw materials was approximately Rp 25,000 per liter, with a potential profit margin of 40%. Participants began marketing their products to church members, nearby stalls, and through social media platforms such as TikTok and WhatsApp. However, within two months only 20 bottles had been sold, indicating that further education on the distinctiveness of liquid soap compared to conventional detergent is needed. This training was grounded in James 2:17, which affirms that faith without action is dead, reflecting the church's calling to empower its congregation not only through preaching but through practical life skills.